Culture wars in America : an encyclopedia of issues, viewpoints, and voices - Chapman, Roger, 1960-; Ciment, James (Armonk, New York : M.E. Sharpe, 2014)
"The term "culture wars" refers to the political and sociological polarization that has characterized American society the past several decades. This new edition provides an enlightening and comprehensive A-to-Z ready reference, now with supporting primary documents, on major topics of contemporary importance for students, teachers, and the general reader. It aims to promote understanding and clarification on pertinent topics that too often are not adequately explained or discussed in a balanced context. With approximately 640 entries plus more than 120 primary documents supporting both sides of key issues, this is a unique and defining work, indispensable to informed discussions of the most timely and critical issues facing America today." -- Publisher's website.
V. 1. A-K -- v. 2. L-Z -- v. 3. Documents, index.
Includes bibliographical references and index.
Keywords: Culture conflict -- Encyclopedias; Politics and culture -- Encyclopedias; Social problems -- Encyclopedias; Social conflict -- Encyclopedias; Ethnic conflict -- Encyclopedias; Culture conflict -- United States -- Encyclopedias; Politics and culture -- United States -- Encyclopedias; Culture conflict; Ethnic conflict; Politics and culture; Social conflict; Social problems; United States; Encyclopedias